2022
DOI: 10.1128/mbio.02944-22
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Pathobiological Role of the Fungal KEOPS Complex in Cryptococcus neoformans

Abstract: The cellular function and structural configuration of the KEOPS complex have been elucidated in some eukaryotes and archaea but have never been fully characterized in fungal pathogens. Here, we comprehensively analyzed the pathobiological roles of the KEOPS complex in the globally prevalent fungal meningitis-causing pathogen C. neoformans .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…1D ), mirroring that of its S. cerevisiae counterpart, which is known to localize in the cytoplasm, nucleus, and mitochondria ( 15 ). This uniform distribution is also consistent with earlier observations regarding the C. neoformans KEOPS complex ( 14 ). Importantly, reintroducing the SUA5-mRuby3 allele into the sua5 Δ mutant successfully restored the wild-type primer extension pattern at position 39 of the Ile tRNA ( Fig.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…1D ), mirroring that of its S. cerevisiae counterpart, which is known to localize in the cytoplasm, nucleus, and mitochondria ( 15 ). This uniform distribution is also consistent with earlier observations regarding the C. neoformans KEOPS complex ( 14 ). Importantly, reintroducing the SUA5-mRuby3 allele into the sua5 Δ mutant successfully restored the wild-type primer extension pattern at position 39 of the Ile tRNA ( Fig.…”
Section: Resultssupporting
confidence: 92%
“…We then examined whether Sua5 plays an expected role in t 6 A tRNA modification via its involvement in TC-AMP biosynthesis. Building upon our previous work, which highlighted the role of the KEOPS complex in t 6 A tRNA modification ( 14 ), we conducted a primer extension analysis using t 6 A-containing tRNA (Ile AAU) extracted from wild-type, bud32 Δ, and sua5 Δ strains. The primer extension profiles revealed that the sua5 Δ mutant closely resembled the bud32 Δ but markedly diverged from the wild-type strain at nucleotide position 39, corresponding to position 37 in the S. cerevisiae tRNA (Ile AAU) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations